Methodological Verification-based Screening of the Representative Ingredients for Traditional Chinese Medicine: Taking Astragalus as an Example for Interfering with Cervical Cancer - Sun, Hao; Wang, Dan; Xu, Mengjin; Gao, Yi; Li, Fan (Current Computer - Aided Drug Design, 2022)
Background: The screening of effective ingredients is the bridge between the research of efficacy and the mechanism of traditional Chinese medicine. Although promising virtual screening has emerged as an attractive alternative, an ideal strategy is still urgently required due to the characteristics of multi-ingredients and multi-targets of traditional Chinese medicine. Objective: The aim of the study was to develop a methodological verification-based novel screening strategy capable of comprehensively assessing the ability of compounds to perturb disease networks, thereby identifying representative ingredients of traditional Chinese medicine interventions in complex diseases. Methods: In this article, we take astragalus interfering with cervical cancer as an example. First, a multifunctional clustering disease network model was constructed; second, the several drugs and their decoys were used for molecular docking with disease network clusters for methodological verification and determining the best scoring criteria. Third, the representative ingredients of astragalus were screened according to the best scoring criteria. Finally, the effects of the representative ingredients on cervical cancer SiHa cells were evaluated by CCK-8 assay, flow cytometry, and western blot analysis. Results: Three representative ingredients of astragalus were betulinic acid, hederagenin and methylnissolin, which perturbed the apoptosis, stabilization of p53, and G1/S transition cluster as a whole, respectively. CCK-8 assay showed that the IC50 value of betulinic acid, hederagenin and methylnissolin at 48 h was 28.84, 101.90, and 187.40 μM, respectively. Flow cytometry showed that these three representative ingredients could significantly induce early apoptosis and cell cycle arrest. Western blot analysis showed that betulinic acid treatment significantly increased p53 expression, while hederagenin and methylnissolin did not. Conclusion: This study has provided new ideas for the screening of effective ingredients in traditional Chinese medicine, and established a foundation for elucidating the overall mechanism of action of traditional Chinese medicine.
Keywords: cervical cancer